EFEK MEDIASI LITERASI DIGITAL PADA PENGARUH KOMPETENSI GURU TERHADAP HASIL BELAJAR SISWA - Fazar, Fazar Nuriansyah; Eeng Ahman, Eeng Ahman; Disman, Disman (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Student learning outcomes in the cognitive domain are dominated by achievements below the Minimum Completion Criteria (KKM) and the inconsistency of previous research results is the background of this study. The purpose of this study is to determine the effect of teacher competence on student learning outcomes and to determine the effect of digital literacy on the influence of teacher competence on learning outcomes. The research method used is an explanatory method using questionnaires and documentation in data collection. The data analysis technique uses a causal step strategy. The results of the study indicate that teacher competence has a positive effect on student learning outcomes and digital literacy mediates the effect of teacher competence on student learning outcomes